Up-flow anaerobic sludge blanket bioreactor for the production of carboxylates: effect of inocula on process performance and microbial communities - Adrián Lago; Silvia Greses; Inés Moreno; Cristina González-Fernández (Bioresources and Bioprocessing)
Abstract This research investigated the acidogenic fermentation (AF) of sugar cane molasses in an up-flow anaerobic sludge blanket (UASB) reactor for the production of carboxylates. The first step was to assess the optimum process temperature (25, 35 or 55 ºC) using two different granular inocula, one from a brewery company (BGS) and other from a paper plant company (PGS). These experiments determined that the most suitable temperature for carboxylates production was 25 ºC, obtaining higher bioconversions (27.3 ± 0.3% using PGS and 39.2 ± 0.2% using BGS), despite the low pH value recorded (4.0-4.2). Then, both inocula were tested in UASB reactors. As a consequence of the operational conditions (25 ºC, pH = 5.5-6, organic loading rate (OLR) = 3 gCOD·L-1·d-1 and hydraulic retention time (HRT) = 10 d), the microbial communities changed from those typical for biogas production to those specialised in the production of volatile fatty acids (VFAs). Indeed, the highest bioconversion efficiency (70.1%) was obtained with BGS, where uncultured Eubacteriaceae family microorganisms (56.0%) prevailed, enhancing the production of butyric acid (59.5 ± 2.4%w/w). Consequently, this inoculum was used to further identify the OLR threshold that should not be exceeded to attain optimal carboxylates production. OLR of 6 gCOD·L-1·d-1 resulted in a decrease in bioconversion efficiency (59.5%). The VFAs pool was dominated by butyric acid (63.0 ± 1.4%w/w at an OLR of 4.5 gCOD·L-1·d-1 and 52.8 ± 2.2%w/w at 6 gCOD·L-1·d-1). The microbial community became even more specialised, increasing the presence of Firmicutes and Actinobacteriota phyla, proving that the imposed conditions favoured the production of VFAs when operating semicontinuously fed UASB reactors.